2021
DOI: 10.1038/s41467-021-27321-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of SETD5-containing NCoR–HDAC3 complex determines enhancer activation for adipogenesis

Abstract: Enhancer activation is essential for cell-type specific gene expression during cellular differentiation, however, how enhancers transition from a hypoacetylated “primed” state to a hyperacetylated-active state is incompletely understood. Here, we show SET domain-containing 5 (SETD5) forms a complex with NCoR-HDAC3 co-repressor that prevents histone acetylation of enhancers for two master adipogenic regulatory genes Cebpa and Pparg early during adipogenesis. The loss of SETD5 from the complex is followed by enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…One of the main biological functions of HDAC3 is repression of transcription via histone deacetylation (Hogg et al 2021). Researchers have proven that the SETD5-containing NCOR-HDAC3 complex inhibits H3K27 acetylation and enhancer activation of 2 adipogenic genes, Cebpα and Pparγ , early during adipogenesis, which is similar to our findings (Matsumura et al 2021). Furthermore, a previous study showed an increase in inflammatory cytokines in Ncor1 -deficient macrophages when stimulated by PPARγ agonists, thereby exacerbating atherosclerosis (Oppi et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…One of the main biological functions of HDAC3 is repression of transcription via histone deacetylation (Hogg et al 2021). Researchers have proven that the SETD5-containing NCOR-HDAC3 complex inhibits H3K27 acetylation and enhancer activation of 2 adipogenic genes, Cebpα and Pparγ , early during adipogenesis, which is similar to our findings (Matsumura et al 2021). Furthermore, a previous study showed an increase in inflammatory cytokines in Ncor1 -deficient macrophages when stimulated by PPARγ agonists, thereby exacerbating atherosclerosis (Oppi et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Mice were maintained in a temperature-and humidity-controlled environment under a 12 h light/12 h dark cycle (08:00-20:00) at constant temperature (23 °C) with free access to food and water. Animals were fed a normal chow diet (CE-2, CLEA Japan Inc.) from the age of 4 weeks or HFD, consisting of 58.0% fat, 15.0% protein, and 27.0% carbohydrate, from the age of 5 to 7 weeks as described previously [61][62][63] . For chronic cold exposure experiments, animals were single-caged and exposed to 12 °C for one week.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…It belongs to SET-domain lysine methyltransferase superfamily which functions to methylate certain histone lysine residues, resulting in regulating the expression of genes. However, there is evidence that SETD5 lacks the methyltransferase activity but scaffolds a corepressor complex, including HDAC3, NCoR, G9a, and PAF1, which couples selective deacetylation of H3K9ac with methylation of this residue (13)(14)(15). The yeast SET3 and SET4, Drosophila UpSET, and human MLL5 are homologous to SETD5 over their SET domains and, except for SETD5, contain a PHD finger (Figure 1).…”
Section: Structural Features Of Setd5mentioning
confidence: 99%